Cytotoxic Activity of Alpinumisoflavone from Erythrina poeppigiana (Leguminosae) Against Colon Cancer (WiDr), Cervical Cancer (Hela), and Hepatoma Cancer (HepG2) Cells - Tati Herlina; Nayla Haraswati; Riza Apriani; Vicki Nishinarizki; Shabarni Gaffar; Unang Supratman (Bogor Agricultural University, Indonesia, 2019)
Cancer is the second cause of death after cardiovascular diseases in the world. Anticancer prevention used can cause undesirable things. Flavonoids are secondary metabolites derived from natural products that are useful for anticancer treatment. This study was performed to observe the cytotoxic activity of alpinumisoﬂavone from Erythrina poeppigiana, toward cervical cancer (Hela), colon cancer (WiDr), and hepatoma cancer (HepG2) cells. The cytotoxic activity of alpinumisoﬂavone was tested using (3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyltetrazolium bromide) assay. The percentage of cell mortality was calculated and the IC50 was calculated using probit analysis. The result shown that alpinumisoﬂavone has antiproliferative eﬀect to colon cancer (WiDr), cervical cancer (Hela), and hepatoma cancer (HepG2) cells with the value of IC50 are 5.63, 7.18, and 18.08 µg/ml, respectively. Based on the value of IC50 alpinumisoﬂavone is very cytotoxic to colon cancer WiDr cell.